A Guide to food selection, preparation and preservation - Soriano, Nora N. (Manila, Philippines : Rex Book Store, 2007)
This "Guide to food selection, preparation and preservation" is written as an answer to a need to simplified reference for students majoring in home economics, food technology and food nutrition .
Part I. Introduction to Food Preparation -- Part II. Food Preservation -- Part III. Selection, Preparation and Preservation of Selected Food Groups
Includes index.
Keywords: FOOD SELECTION